MODEL PRESTASI KERJA YANG DIPENGARUHI VARIABEL ROTASI DAN MUTASI (Studi Kasus Pada Dinas Sosial Provinsi Jawa Tengah) - Rahayu, Tintin; Mohklas, Mohklas (JAB (Jurnal Akuntansi & Bisnis), 2016)
AbstractHuman resources is one of the important resources in an organization or company. Source amanusia quality day will help the smooth running of the organization and achieving goals. Quality human resources indicated by the performance achieved. It can encourage the achievement of which is the rotation and mutation. Because it can help improve the knowledge and quality of employees. This study aims to determine whether there is influence between the rotation and the mutation of the job performance of employees Social Service Central Java Province. The method used is multiple linear regression analysis with a population of 180 employees and 45 employees of the sample of the study. The results showed that rotation and mutation partially or simultaneously significant positive effect on job performance, the t value 6.516 > 1.681 with a significance level of 0.000 for the variable rotation, whereas the mutation variable t value 2.663 > 1.681 with 0.011 significance level. Simultaneous test F count 34.810 > 4.07 with a significance level of 0.000.Keywords: Rotation, Mutations and Job Performance.